Mechanism of dominance of the Breit interaction in dielectronic recombination - Tong, Xiao-Min; Hu, Zhimin; Li, Yueming; Han, Xiaoyin; Kato, Daiji; Watanabe, Hirofumi; Nakamura, Nobuyuki (Journal of physics. B, Atomic, molecular and optical physics, 2015)
The recent theoretical and experimental studies show that the Breit interaction plays a dominant role in the dielectronic recombination for some particular transitions. The detailed mechanism of why the Breit interaction is dominant for such a process is still unknown. In this work, we performed a simulation and decomposed each individual term in the transition matrix level and found that the Breit interaction is dominant when the leading term ( with the larger of r1 and r2) contribution of the two-electron Coulomb interaction is vanished. Based on this mechanism, we explained why the dielectronic capture strength to state is much stronger than the one to as well as why the Breit interaction plays a dominant role in the anisotropic parameters. Furthermore, the present finding may guide us to search some physical processes in which the Breit interaction is dominant by simply analyzing the coupling coefficients for a given isoelectronic sequence.